Maternal Experiences of Racial Discrimination, Child Indicators of Toxic Stress, and the Minding the Baby Early Home Visiting Intervention. Issue 5 (September 2021) - Condon, Eileen M.; Londono Tobon, Amalia; Jackson, Brianna; Holland, Margaret L.; Slade, Arietta; Mayes, Linda; Sadler, Lois S.
Abstract : Background: Racism is a significant source of toxic stress and a root cause of health inequities. Emerging evidence suggests that exposure to vicarious racism (i.e., racism experienced by a caregiver) is associated with poor child health and development, but associations with biological indicators of toxic stress have not been well studied. It is also unknown whether two-generation interventions, such as early home visiting programs, may help to mitigate the harmful effects of vicarious racism. Objective: The purpose of this study was to examine associations between maternal experiences of racial discrimination and child indicators of toxic stress and to test whether relationships are moderated by prior participation in Minding the Baby (MTB), an attachment-based early home visiting intervention. Methods: Ninety-seven maternal–child dyads ( n = 43 intervention dyads, n = 54 control dyads) enrolled in the MTB Early School Age follow-up study. Mothers reported on racial discrimination using the Experiences of Discrimination Scale. Child indicators of toxic stress included salivary biomarkers of inflammation (e.g., C-reactive protein, panel of pro-inflammatory cytokines), body mass index, and maternally reported child behavioral problems. We used linear regression to examine associations between maternal experiences of racial discrimination and child indicators of toxic stress and included an interaction term between experiences of discrimination and MTB group assignment (intervention vs. control) to test moderating effects of the MTB intervention. Results: Mothers identified as Black/African American (33%) and Hispanic/Latina (64%). In adjusted models, maternal experiences of racial discrimination were associated with elevated salivary interleukin-6 and tumor necrosis factor-α levels in children, but not child body mass index or behavior. Prior participation in the MTB intervention moderated the relationship between maternal experiences of discrimination and child interleukin-6 levels. Discussion: Results of this study suggest that racism may contribute to the biological embedding of early adversity through influences on inflammation, but additional research with serum markers is needed to better understand this relationship. Improved understanding of the relationships among vicarious racism, protective factors, and childhood toxic stress is necessary to inform family and systemic-level intervention.